Cryo-EM structure of human glucose transporter GLUT4 - Yafei Yuan; Fang Kong; Hanwen Xu; Angqi Zhu; Nieng Yan; Chuangye Yan (Nature Communications, 2022)
Small solute carriers remain difficult to study by single particle cryo-EM. Here, the authors report the cryo-EM structure of human insulin-responsive glucose transporter GLUT4 (55 kDa) without rigid soluble domains or binders.